Pengaruh Luas Lahan Panen Padi dan Tenaga Kerja Sektor Pertanian terhadap Produksi Padi di Provinsi Jambi - Susilawati, Esti; Halim, Abd (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of rice harvest area and agricultural sector workforce on rice production in Jambi Province. The type of data collected is secondary data sourced from Jambi in the Jambi Province Central Statistics Agency (CSA) figures in the form of Gross Regional Domestic Product (GRDP) in the agricultural sector of Jambi Province. The research results show that the area of rice harvested land has a significant and positive effect, while agricultural sector labor does not have a significant and negative effect on rice production during the 2010-2022 period.